In Vitro Mutagenesis of Dendrobium gabriella suryajaya Using Ethyl Methane Sulfonate (EMS) and Plantlet Regeneration (Biosaintifika: Journal of Biology & Biology Education, 2023)
Plant breeding through mutation techniques has the main purpose to explore genetic diversity in the presence of useful traits for developing new plants. Ethyl Methane Sulfonate (EMS) is a widely used chemical to induce mutations in plants focused on obtaining genetic variation. EMS can induce random points of mutations and some of which can create new stop codons in the desired gene. EMS has been successfully used to generate morphological diversity and encourage the improvement of desired traits. The 3-month-old Dendrobium gabriella suryajaya Orchid protocorm-like bodies (PLB) treatment with EMS concentrations of 0.025%, 0.05%, and 0.075% can change genetic diversity, especially in leaf morphology. A total of 105 orchids were soaked in EMS solution at concentrations for 12 and 24 hours respectively. The phenotypic variations observed in this population include changes in leaf color and the number of buds. This EMS mutant population will be used for further studies including screening for various traits such as through ISSR analysis to determine the level of diversity. This research shows that mutagenesis using EMS can produce the amount of variability in Dendrobium. The generation of variability for desired traits resulted in the identification of several mutants with important agronomic characteristics that can be used as germplasm for improvement.